Antibacterial Activity of Austroeupatorium inulifolium (Talu Dagang) Leaf Extracts and Fractions Against Staphylococcus aureus and Escherichia coli: Bioactivity-Guided Fractionation and Isolation of the Active Subfraction - Syukriatul Ulya; Masfria Masfria; Alfi Khatib (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Background: Infectious diseases caused by pathogenic bacteria, including Staphylococcus aureus and Escherichia coli, pose significant public health challenges, necessitating the exploration of alternative plant-based therapies. Objective: This study aimed to evaluate the antibacterial efficacy of Talu Dagang (Austroeupatorium inulifolium) leaf extracts and fractions and to identify the most bioactive subfraction through preparative isolation. Methods: Dried leaves were macerated with ethanol and partitioned using n-hexane and ethyl acetate. Antibacterial activity was assessed by agar well diffusion (MIC) and dilution (MBC) methods. The most active fraction was further fractionated by preparative thin-layer chromatography (PTLC), and subfractions were screened for antibacterial activity. Results: The ethyl acetate fraction showed the highest antibacterial activity, with an MIC of 5 mg/mL and MBC of 2.5 mg/mL against S. aureus. PTLC yielded ten subfractions (refined to seven), with subfraction 6 exhibiting the greatest potency (inhibition zone 8.6 mm at 500 mcg/mL) against S. aureus. Activity against E. coli was limited across all preparations. Conclusion: Talu Dagang leaf extracts, particularly the ethyl acetate fraction and its subfraction 6, possess significant antibacterial properties supporting the plant’s traditional medicinal use and potential development as a natural antimicrobial agent.